2023
DOI: 10.1017/s2045796023000100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 pandemic on utilisation of community-based mental health care in North-East of Italy: A psychiatric case register study

Abstract: Aims WHO declared that mental health care should be considered one essential health service to be maintained during the coronavirus disease 2019 (COVID-19) pandemic. This study aims to describe the effect of lockdown and restrictions due to the COVID-19 pandemic in Italy on mental health services’ utilisation, by considering psychiatric diagnoses and type of mental health contacts. Methods The study was conducted in the Verona catchment area, located in the Veneto region (northeastern It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The number of psychiatric day care facilities used was also significantly smaller in the months during the period of emergency declarations and priority preventative measures than in other months in FY 2020-2021. Previous studies outside Japan have reported that the number of services for outpatients with mental illness and rehabilitation needs, including psychiatric day care, has decreased since 2020 owing to the COVID-19 pandemic-related lockdown [18,19]. Our results were consistent with this, suggesting that the number had decreased due to effects such as staying at home and the operational scale of facilities; this trend continued in FY 2021.…”
Section: Discussionsupporting
confidence: 88%
“…The number of psychiatric day care facilities used was also significantly smaller in the months during the period of emergency declarations and priority preventative measures than in other months in FY 2020-2021. Previous studies outside Japan have reported that the number of services for outpatients with mental illness and rehabilitation needs, including psychiatric day care, has decreased since 2020 owing to the COVID-19 pandemic-related lockdown [18,19]. Our results were consistent with this, suggesting that the number had decreased due to effects such as staying at home and the operational scale of facilities; this trend continued in FY 2021.…”
Section: Discussionsupporting
confidence: 88%
“…It is possible that having a green space near the living apartment but not being able to access it due to COVID-19 restrictions could be an additional mental health stressor [ 58 , 59 ]. This evidence should also consider the fact that, on one side, the availability of the services was reduced during the pandemic as many facilities, in particular rehabilitation services and daycare, were closed to reduce contagion, and, on the other side, people were hesitant to visit the services in person during the pandemic [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…All types of contacts (with psychiatrists, psychologists, nurses, psychiatric rehabilitation therapists, occupational therapists, and social workers) provided by mental health services were included. A comprehensive description of the study setting and clinical data sources can be found in a recently published article [ 41 ]. Our current study narrows its scope to the Verona municipality, diverging from the catchment area discussed in the previous publication and integrating environmental variables, an aspect previously omitted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there was a reduction in the number of patients attending mental health outpatient services (10,(12)(13)(14). In Italy, this was partly consequent to the reduced opening hours or temporary closure of outpatient community mental health centers (15).…”
Section: Introductionmentioning
confidence: 99%